Triage implementation in Pakistan: a case of broken healthcare system - Mansoor, Misha; Shafiq, Muhammad Hamza; Khalid, Mubashra (Journal of the Pakistan Medical Association, 2024)
Madam, The death toll due to road traffic accidents (RTA) in Pakistan reached 28,170 in 2020, according to WHO. This accounts for 1.93% of all deaths in the World. (1) Mortality due to RTA is an ever-increasing concern and its management, especially in Pakistan, is still a bigger concern. The efficient way of dealing with Trauma is by following globally accepted evidence-based “Advanced Trauma Life Support” guidelines. Triage being the first step in ATLS literally means “to sort”. In other words, identifying the greatest good for greatest numbers. The Emergency Department (ED) rule must be to manage patients based on the severity of problems and not on the order of arrival. Death can be prevented in the patients who benefit the most by getting medical attention the earliest. All the patients escorted and rescued from the place of incident should be sorted rapidly and given a colour-coded tag based on urgency. Onsite triage is the most critical life saving measure. A Karachi based study concluded that most paramedics in ambulances had poor knowledge of pre-hospital management and 72.3% thought they could not do triage. (2) Similarly, another study at the emergency department of a tertiary care hospital in Karachi showed concerningly poor knowledge of triage.(3) Only 5 CPSP accredited public hospitals in Pakistan have emergency medicine as a separate field which results in lack of triage implementation as EDs of most hospitals are run by internal medicine professionals and general surgeons. Simply, implementing triage has shown to reduce and ED mortality (by 3.80%), resources’ utilisation, and length of stay.(4) Punjab, the development hub of Pakistan, provides 22 public hospitals, including only 12 fully functional ones, for dealing with trauma patients. DHQs bearing the burden of all trauma patients of districts are level-III trauma centres lacking in specialised surgical care and categorization of paediatric and adult patients. Other independent trauma care facilities are level-IV trauma centres which act as a relay to stabilise the patients before they are transferred to a better facility. A level-I trauma centre alone can increase 25% survival rate of trauma patients, but unfortunately Pakistan does not have a single level-I trauma centre. (5) Therefore, all Rescue staff must be trained regularly for future enactment of triage to alleviate RTA associated mortality along with upgrading of trauma centres to level-I.